Patients, clinicians and researchers working together to improve cardiovascular health: a qualitative study of barriers and priorities for patient-oriented research. Issue 2 (6th February 2020) - Santana, Maria-Jose; Zelinsky, Sandra; Ahmed, Sadia; Doktorchik, Chelsea; James, Matthew; Wilton, Stephen; Quan, Hude; Fernandez, Nicolas; Anderson, Todd; Butalia, Sonia
Abstract : Objectives: The overall goal of this study is to identify priorities for cardiovascular (CV) health research that are important to patients and clinician-researchers. We brought together a group of CV patients and clinician-researchers new to patient-oriented research (POR), to build a multidisciplinary POR team and form an advisory committee for the Libin Cardiovascular Institute of Alberta. Design: This qualitative POR used a participatory health research paradigm to work with participants in eliciting their priorities. Therefore, participants were involved in priority setting, and analysis of findings. Participants also developed a plan for continued engagement to support POR in CV health research. Setting: Libin Cardiovascular Institute of Alberta, Cumming School of Medicine, University of Calgary, Canada. Participants: A total of 23 participants, including patients and family caregivers (n=12) and clinician-researchers (n=11). Results: Participants identified barriers and facilitators to POR in CV health (lack of awareness of POR and poor understanding on the role of patients) and 10 research priorities for improving CV health. The CV health research priorities include: (1) CV disease prediction and prevention, (2) access to CV care, (3) communication with providers, (4) use of eHealth technology, (5) patient experiences in healthcare, (6) patient engagement, (7) transitions and continuity of CV care, (8) integrated CV care, (9) development of structures for patient-to-patient support and (10) research on rare heart diseases. Conclusions: In this study, research priorities were identified by patients and clinician-researchers working together to improve CV health. Future research programme and projects will be developed to address these priorities. A key output of this study is the creation of the patient advisory council that will provide support and will work with clinician-researchers to improve CV health.